Tissue-engineered canine mitral valve constructs as In vitro research models for myxomatous mitral valve disease - Liu, Mengmeng (The University of Edinburgh, 2014)
Myxomatous mitral valve disease (MMVD) is one of the most common degenerative cardiac diseases affecting humans and dogs; however, its pathogenesis is not completely understood. This study focussed on developing tissue-engineered fibrin based canine mitral valve constructs, which can be used as an in vitro platform to study the pathogenesis of MMVD. Prior to three dimensional (3D) construct fabrication, primary canine mitral valve endothelial cells (VECs) and valve interstitial cells (VICs) were isolated, cultured and characterized utilising a variety of techniques. Moreover, preliminary experiments were carried out to optimise the purity of VEC cultures. It is uncertain if canine MMVD is initiated by long term shear stress damage to the valve endothelium or from abnormalities of VICs. To investigate both hypotheses, three types of models were produced using fibrin/based 3D culture techniques: healthy VEC-VIC co-culture (Type 1); healthy VEC-diseased VIC co-culture (Type 2); healthy VEC-VIC co-culture with endothelial damage during culture (Type 3). Histological examination demonstrated partial native tissue-like morphology of the 3D constructs. Results suggest that current static cultured constructs express MMVD markers irrespective of using healthy or diseased VICs. Simple mechanical stimulation was found to regulate VIC activity in the 3D models. Endothelial damage resulting in VIC phenotypic activation (a change typically observed in MMVD), and decreased mechanical tension appeared to be a negative regulator of this effect. Moreover, there appears to be heterogeneity in the activated VIC population. Additionally, distinct advanced glycation end product (AGE) carboxymethyllysine (CML) expression was found in canine MMVD valves, which suggesting this biochemical compound (known to affect long living protein) might be a putative regulator of MMVD pathogenesis. The role of CML in MMVD can be further investigated utilizing current 3D static mitral valve construct model in future studies. Lastly a prototype dynamic tubular construct and a customised bioreactor system were developed. Preliminary data suggest the feasibility of tubular construct fabrication and endothelialisation, which provides foundation for future dynamic conditioning experiments and will allow examination of the role of endothelial shear stress in triggering MMVD. In summary, this project successfully developed fibrin based canine mitral valve constructs. It is believed they are promising models for MMVD research, allowing new insights in understanding MMVD pathogenesis.
Keywords: myxomatous mitral valve disease; MMVD; degenerative cardiac diseases; fibrin; valve interstitial cells; valve endothelial cells; canine mitral valve